Penyesuaian Diri Pada Mahasiswa Non Muslim di Kampus Islam - Ahmad Hidayat; Rahmad Muliadi (Journal of Islamic and Contemporary Psychology (JICOP), 2022)
This study aims to examine and explore the process of self-adjustment of non-Muslim students studying at the Islamic Education Institute Foundation (YLPI) Faculty of Psychology, Islamic University of Riau. A phenomenological qualitative approach is used in this study. The participants of this study were 2 students and 1 female student of the psychology faculty who are Christian and come from the Batak and Minahasa ethnic groups, who are currently studying in semesters I, V and VII. The results of the research show that carrying out the process of adjustment by conformity, fostering positive perceptions, motivating oneself to learn, conducting effective communication, building relationships, and being active in self-development activities. Then the desire to become a psychology graduate from a quality campus, the dispensation of college lecturers teaching Islamic subjects, an atmosphere of campus life that is full of tolerance for religious and cultural differences, as well as non-discriminatory social support, makes non-Muslim students able to adapt to existing policies at UIR, and feel comfortable studying at the psychology faculty of Universitas Islam Riau.